Identification and experimental validation of ferroptosis-related gene lactotransferrin in age-related hearing loss - Zeng, Chaojun; Gu, Xi; Chen, Yuqing; Lin, Yanchun; Chen, Junying; Chen, Zhifeng; Chen, Chenyu; Yao, Guangnan; Lin, Chang (Frontiers in Aging Neuroscience, 2024)
Objective To reveal the relationship between ARHL and ferroptosis and screen ferroptosis-related genes (FRGs) in ARHL. Methods Bioinformatics were used to analyze the hub genes and molecular mechanism of ferroptosis in the aging cochleae. Senescence β-galactosidase staining, iron content detection, and micro malondialdehyde (MDA) assay kits were used to measure β-galactosidase activity, and expression of Fe2+ and MDA, respectively. Fluorescence microscope was used for immunofluorescence assay of hub genes. Western blot was used to verify the expression of hub genes in HEI-OC1 cells, cochlear explants, and cochleae of C57BL/6J mice. Data were expressed as mean ± SD of at least three independent experiments. Results The analysis of bioinformatics confirmed that lactotransferrin (LTF) is the hub gene and CEBPA-miR-130b-LTF network is the molecular mechanism for cochlear ferroptosis. Compared with the control group, the experiments proved that the indicators of ferroptosis, including Fe2+, MDA, and LTF were differentially expressed in aging HEI-OC1 cells, aging cochlear explants, and aging cochleae. Conclusion These results demonstrate that ferroptosis plays an important role in ARHL, and LTF is a potential therapeutic target for ARHL via regulating cochlear ferroptosis.